Studi Kasus: Analisis Pengendalian dan Manajemen Risiko Kesehatan dan Keselamatan Kerja di Rumah Sakit (K3RS) - Irgi Biantara; Dyah Kusumastuti (Pusat Riset dan Inovasi Nasional, 2023)
Risk management as a process for analysis, identification, evaluation, control, and overcoming risks faced by organizations or Hospital Agencies. This control is carried out by implementing Hospital Work Safety Health (HWSH). The purpose of this case study is to find out the analysis of occupational health and safety risk control and management in hospitals. The method in the case study is by implementing the Hospital Occupational Health Safety Risk Management system (HOH SRMS). Hospital management system as a whole which includes the organizational structure, planning, responsibilities, implementation, procedures, processes and resources needed for the development, implementation, achievement and maintenance of occupational health and safety policies. The results of the analysis state that the Occupational Safety & Health (OSH) plan in the hospital is the key as a reference for performance in health worker safety with risk identification, risk analysis, risk assessment, implemented solutions, and risk monitoring. It can be concluded that risk management in hospitals is a comprehensive control activity in the form of identification and evaluation to reduce the risk of injury and loss to patients, hospital employees and to improve the quality of health services. Hospital Agencies have the duty and obligation to identify and control thoroughly both in the service area, infectious area and hospital environment area. HOH SMRS as an important aspect designed to prevent negative impacts on business processes or minimize financial loss. It is hoped that the hospital will carry out risk management by identifying weaknesses in the system and correcting these weaknesses.